PELATIHAN PEMBUATAN PRODUK KREATIF BERBAHAN DASAR SAMPAH BAGI IBU-IBU PEKERJA SEKTOR INFORMAL - Novianto, Victor; Nafiah, Daimatun; Kristiyanti, Iin (Universitas Negeri Yogyakarta, 2013)
Hadroh group Padhang Ati (Enlightened Heart) was a musical group formed by household-wives who lived around Bener Village, District of Tegalrejo, Municipality of Yogyakarta. They worked in informal sector, as building-craftsperson and housemaid, and sang with traditional instruments, such as rebana in this group. In order to fill in their spare time with profitable activity, Science for Society Team (IbM Team) proposed trash recycle as an activity for these women. IbM Team delivered training in three stages as the method, firstly, plastic trash recycle training, secondly, organizational training, and thirdly, human resource training for the women. In result the women from Hadroh group Padhang Ati had enough knowledge, skill, and attitude to recycle plastic trash and organize the marketing by themselves. They accomplished the training goals, i.e. 1) Able to recycle plastic trash into shredded-plastic; 2) Able to organize this activity through modern organization, which was credit union; 3) Able to manage this organization, from administration, organization, entrepreneurship, and marketing sustainably. For example, they sold hotel slippers made of recycled materials to local hotel in Yogyakarta. They also benefitted from the credit unions by lending money and returned it with either money or shredded-plastic. Keyword: coop, women empowerment, trash recycle, entrepreneurship